Generalized Anxiety Disorder- A Voice from Lived Reality: Viewpoint - Poudel , Siddhartha; Parajuli , Apekshya (Journal of Karnali Academy of Health Sciences, 2025)
This viewpoint article is a personal narrative of a generalized anxiety disorder (GAD) experience, reflecting the lived reality of denial, awareness, and acceptance of mental illness. It emphasizes early intervention, breaking down stigma, and that recovery is not a linear process. The story brings to life how invisible mental illness can feel, how hard it is to put a name to the struggle, and how therapy and support can slowly bring a sense of hope and healing. It also encourages free dialogue on mental health to foster compassion and reduce stigma. With the use of personal experience and global definitions of mental health, the article focuses on the fact that anxiety struggles are real, valid, and require attention. These reflections are meant to remind anyone walking a similar path to trust their healing, however slow or uneven it may feel. They are also an invitation to open up conversations about mental health, so that it becomes something we discuss with honesty and compassion, rather than silence and stigma.